2013
DOI: 10.1177/0018720813506223
|View full text |Cite
|
Sign up to set email alerts
|

Situation Awareness Recovery

Abstract: We interpret these findings in terms of the memory-for-goals model, which suggests that SAR consists of increased scanning in order to compensate for decay, and previously viewed cues act as associative primes that reactivate memory traces of goals and plans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 26 publications
1
49
1
Order By: Relevance
“…Endsley (1995) showed that participants were able to retain SA for a multi-item display task for up to 5 min after an interruption during which no task changes occurred. Other research has shown that individuals are able to accurately locate the preinterruption positions of multiple display objects following short-term interruption (Gartenberg, Breslow, McCurry, & Trafton, 2013;Ratwani & Trafton, 2008) and can do so more accurately than finding the new positions of displaced objects (Hunter & Parush, 2010).…”
mentioning
confidence: 99%
“…Endsley (1995) showed that participants were able to retain SA for a multi-item display task for up to 5 min after an interruption during which no task changes occurred. Other research has shown that individuals are able to accurately locate the preinterruption positions of multiple display objects following short-term interruption (Gartenberg, Breslow, McCurry, & Trafton, 2013;Ratwani & Trafton, 2008) and can do so more accurately than finding the new positions of displaced objects (Hunter & Parush, 2010).…”
mentioning
confidence: 99%
“…According to the MFG theory, an interruption would lead to significant drops in situation awareness on the interrupted task and will induce situation awareness recovery after the interruption (cf. Gartenberg et al, 2013). Hence, we expect a worsening of performance in conditions with interruption as compared to conditions without interruption.…”
Section: The Present Researchmentioning
confidence: 88%
“…SAR is the process of restoring situation awareness (SA) after it has been reduced (Gartenberg et al, 2013. Gartenberg et al (2013 describe this process with the example of a task where multiple objects, for example unmanned aerial vehicles, have to be monitored simultaneously.…”
Section: Situation Awareness Recovery (Sar)mentioning
confidence: 99%
See 1 more Smart Citation
“…If an increased workload underlies the degraded SA, the system could adaptively respond by dynamically reallocating task demands, freeing up cognitive resources, and thereby allowing the cognitive processes necessary for SA recovery to begin [41]. Alternatively, if a low workload is identified, the response might be to increase task demands as boredom and low workload exacerbate degradation of SA [42].…”
Section: Bmentioning
confidence: 99%